Water Scarcity and Social Conflict - Kerstin Unfried; Krisztina Kis-Katos; Tilman Poser (Institute of Labor Economics (IZA), 2021)
Climate change and the increasing demand of water intensify the global water cycle, altering the distribution of water in space and time. This is expected to result in wet areas getting wetter and dry areas getting drier (Pan et al., 2015). As water is key to life, water scarcity is likely to provoke conflict. Using grid-cell data for Africa and central America over the years of 2002 to 2017, we establish a causal empirical link between the likelihood of local conflict and water mass declines. We measure water mass anomalies based on changes in Earth's gravity field recorded by GRACE and link them to social conflict events recorded in the SCAD data. To account for potential endogeneity in the demand for water, we instrument water mass change by the interaction of the number of drought months per year with yearly global average temperature changes. Our results show that a one standard deviation decrease in local water mass that follows from droughts and an intensifying water cycle more than triple the local likelihood of social conflict. Access to groundwater and surface water helps to mitigate these effects substantially. Water demand factors contribute to a quicker depletion of water mass in case of drought shocks, but do not intensify the link between water decline and conflict itself.
Keywords: D74; Q25; Q54; 330; social conflict; water scarcity; climate change